Culturally-Based Islamic Religious Education: Controversies, Changes, and Trends Toward Achieving the SDGs in the Modern Era - Zulfi Ida Syarifah; Fajar Syarif; Saif Uddin Ahmed Khondoker (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study explores the implementation of culturally-based Islamic Religious Education (IRE) as a transformative effort to support the achievement of the Sustainable Development Goals (SDGs), particularly in promoting inclusive, equitable, quality education and fostering peaceful, just, and inclusive societies. The main objective is to examine how cultural integration is applied within IRE practices in schools, how it is perceived by various stakeholders, and its impact on students’ religious understanding, tolerance, and identity formation. Theoretical framework: Drawing upon a theoretical framework rooted in multicultural education and identity theory, the research highlights the significance of integrating local cultural values into religious education to prevent radicalization and foster a more inclusive worldview among students. Literature review: The literature review involves a critical analysis of academic works that address controversies, pedagogical shifts, and trends in culturally-based IRE. Methods: The method employed is a qualitative literature study that synthesizes findings from scholarly publications focused on cultural adaptation in Islamic education. Results: Results reveal three key findings: (1) persistent debates among scholars and educators regarding the inclusion of cultural elements in religious teaching, ranging from enthusiastic support to strong rejection; (2) a notable shift in IRE delivery methods from traditional classroom instruction to digital and technology-based formats, aligning with global educational trends; and (3) the potential of culturally-based IRE to serve as an effective countermeasure to religious radicalism and identity fragmentation among students in the modern era. Implications: The implications of this research extend to both theoretical enrichment and practical implementation. It offers a conceptual contribution to understanding the dynamics of cultural integration in religious education, while also providing actionable insights for teachers, schools, and policymakers to develop pedagogical strategies that are inclusive, adaptive, and socially responsive. Novelty: The novelty of this study lies in its emphasis on cultural integration as a strategic and sustainable model for Islamic education reform that aligns with the broader vision of the SDGs. By contextualizing religious values through cultural frameworks, this approach reinforces peaceful coexistence, identity stability, and educational inclusivity.